A novel approach for determination of nucleation rates and interfacial energy of metallic magnesium nanoclusters at high temperature using non-isothermal TGA models. (16th January 2023) - Srivastava, Prachi; Sabbarwal, Shivesh; Verma, Vivek Kumar; Kumar, Manoj
Highlights: Precisely computed high-temperature kinetic barrier (Jo) of nucleation using Vyazovkin AIC method. Thermogravimetric data was extracted from magnesium nanoclusters (∼1 nm). Nucleation rate, frequency factor, ΔG, ΔH, and ΔS and interfacial surface energy of indigenously prepared magnesium nanoclusters was also estimated. Four different models were proposed for the computation of nucleation rate and interfacial energy of Magnesium nanoclusters. Abstract: The exploration of temperature-dependent nucleation is required to appraise the extent of kinetic and thermodynamic barriers associated with the origin of subatomic size nuclei, which controls the nucleation rate. The precise computation of nucleation rate, thermodynamic parameters, and interfacial surface energy for ultra-small nanoclusters (0.5–2 nm) is still absent in the high-temperature range. Here, apparent activation energy ( Ea ), thermodynamic parameters ( ΔG, ΔH, and ΔS ), and pre-exponential kinetic factor were estimated by utmost accurate Vyazovkin advanced, and KAS isoconversional techniques for calculation of nucleation rate and interfacial energy for ultra-small magnesium nanoclusters (∼0.8 ± 0.24 nm), in the temperature range from 555 to 780 K. The master plots propounded the existence of third order random nucleation in magnesium metal matrix over a specified conversion. Based on the above findings, four mathematical models are proposed to compute nucleation rate and interfacial energy in magnesium clusters over respective temperatures and conversions. These models are beneficial for predicting the nucleation rate and interfacial energy over a high range of temperature and specific conversion.